Kønsrepræsentation i politik - Den kvindelige politiker: Statsborger eller kønsvæsen? - Bonde, Hans (Politik, 2015)
Over the last few decades the concept of equal opportunities has imperceptibly shifted from being a struggle for equality in its initial position to being a struggle for equality in its nal position, aimed at a balance of an ideal 50 per cent to the so-called ‘under-represented sex’. In aiming to achieve a ‘gender balance’ between the two sexes in national and EU commission politics the struggle has become one of gender representation on behalf of women as a group. A notable shift has thus taken place from the initial idea of enlightened modernity about the inviolability of the individual to the inviolability of a collective sex and the right to a speci c share of positions at the elite level.